Occupation and male infertility: glycol ethers and other exposures. Issue 10 (16th April 2008) - Cherry, N; Moore, H; McNamee, R; Pacey, A; Burgess, G; Clyma, J-A; Dippnall, M; Baillie, H; Povey, A
Abstract : Objectives: To investigate the relation between male infertility and occupational exposures, particularly glycol ethers. Methods: A case-referent study was designed in which men attending 14 fertility clinics in 11 centres across the UK in 1999–2002 were recruited following 12 months of unprotected intercourse and without a previous semen analysis. Cases were those with low motile sperm concentration (MSC) relative to the time since their last ejaculation (MSC <12×106 for 3 days of abstinence). Referents were other men attending these clinics and meeting the inclusion criteria. A single semen sample was collected at the clinic and analysed at the andrology laboratory serving each hospital. Concentration was determined manually with motility assessed centrally from video recordings. Exposures and confounding factors were assessed from self-completed and nurse–interviewer questionnaires, completed prior to the results of the semen analysis. The occupational histories were assessed for exposures relative to UK norms by a team of occupational hygienists blind to case status. Results: Of 2118 men in employment at the time of the interview, 874 (41.3%) were cases. Work with organic solvents, particularly glycol ethers, in the 3 months before the first clinic visit was associated with the likelihood of low motile sperm count. Unadjusted odds ratios (OR) for moderate and high glycol ether exposure (compared with none) were 1.70 (95% CI: 1.11 to 2.61) and 2.54 (95% CI: 1.24 to 5.21). Adjustment for potential confounders (surgery to the testes, previous conception, wearing boxer shorts, drinking alcohol, employed in manual work) reduced the risk associated with glycol ether exposure: moderate OR = 1.46 (95% CI: 0.93 to 2.28), high OR = 2.25 (95% CI: 1.08 to 4.69). No other occupational risk factor was identified. Conclusions: Glycol ether exposure was related to low motile sperm count in men attending fertility clinics. This suggests that, at the time of the study, glycol ethers continued to be a hazard for male fertility.